2022
DOI: 10.1097/bot.0000000000002148
|View full text |Cite
|
Sign up to set email alerts
|

Management of Vancouver B2 Periprosthetic Femoral Fractures, Revision Total Hip Arthroplasty Versus Open Reduction and Internal Fixation: A Systematic Review and Meta-Analysis

Abstract: Objective: To identify and analyze the current evidence for the use of open reduction and internal fixation (ORIF) constructs compared with conventional revision total hip arthroplasty (rTHA) for the management of Vancouver B2 periprosthetic femoral fractures (PFFs).Data Sources: A systematic literature search of the MEDLINE, CINAHL, and EMBASE databases was conducted. Prospective and retrospective studies were eligible. No limitation was placed on publication date, with only articles printed in English eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…While RA is likely to remain the mainstay of treatment, ORIF should be considered in patients where RA is not ideal. Furthermore, the results show that if ORIF is performed, the outcomes are not disastrous as convention would have us believe and may offer a benefit over RA, although further research will help identify patients who may benefit from ORIF over RA (10).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…While RA is likely to remain the mainstay of treatment, ORIF should be considered in patients where RA is not ideal. Furthermore, the results show that if ORIF is performed, the outcomes are not disastrous as convention would have us believe and may offer a benefit over RA, although further research will help identify patients who may benefit from ORIF over RA (10).…”
Section: Introductionmentioning
confidence: 82%
“…Recently, there has been a debate on the need to follow these recommendations in all patients. Various authors have argued that, in certain circumstances, VB2 PPHF could be successfully treated using the ORIF technique (3,8,9,10). For this reason, in some studies, ORIF has been compared to revision arthroplasty (RA) for this type of fracture, and equivalent if not better results have been obtained (8,11,12,13,14,15,16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, RA was thought to be the only possible treatment for Vancouver B2 fractures but newer evidence suggests that ORIF is a viable treatment option in select cases [ 3 , 6 – 8 , 12 , 13 ]. A recent review with pooled data from 1622 patients treated for Vancouver B2 fractures found that 21% of the patients were treated with ORIF.…”
Section: Discussionmentioning
confidence: 99%
“…The overall revision rate was 14% and 18% after RA and ORIF, respectively. The dislocation rate after RA was higher than after ORIF but with regard to other complications and reoperation rates, there was no significant difference between RA and ORIF [ 12 ]. Another large review with pooled data from 2509 patients included both Vancouver B2 and B3 fractures.…”
Section: Discussionmentioning
confidence: 99%